The characteristics of political relations between the Arab and the Persian during the reign of the sassane kings "Ardashir the first, shahbour the first, shahbour the second, Bahram the fifth; kisra Anushrwan and kisrah Abruis" as amodel - بيداء جبار محمد (College of Education for Women, 2019)
This paper depends on sheding some litgt on the characteristics of political relations between the arab and the Persian during the reign of sassane kings. "Ardashir the first, shahbour the first, shahbour the second, Bahram the fifth; kisra Anushrwan and kisrah abruis" And who rulled the Persian before the Islamic conquest and were adopted in this studym as a model. It was possible to get some information from invaluable refereces in order to arrive at a clear image as regards the nature of these relations. These relations were differently political according to the circumstances of ruling, interests and the personality of those kings.